Polyaniline/polysulfone ultrafiltration membranes with improved permeability and anti-fouling behavior. (April 2021) - Yuan, Xiao-Tong; Wu, Lei; Geng, Hong-Zhang; Wang, Luda; Wang, Wenyi; Yuan, Xue-Shuang; He, Benqiao; Jiang, Yi-Xuan; Ning, Yu-jie; Zhu, Ze-Ru; Li, Jianxin
Graphical abstract: We fabricate ultrafiltration PANI/PSF blend membranes (PPMs) by a facile phase inversion method with the addition of PANI. Compared with the pristine PSF membrane, PPMs showed better hydrophilicity, water flux, and anti-fouling property. Otherwise, the anti-fouling mechanism was analyzed by the interfacial interaction energy, which were evaluated by applying the XDLVO theory. Calculations prove that there are reduced attractive interaction energies between the PPMs and NOM pollutants molecules in comparison to the interaction between the pristine PSF and NOM pollutants molecules. In theory, it is further confirmed that the anti-fouling performance of the hybrid membrane by blending with PANI has been improved. Our approach represents a convincing theoretical background for understanding the improvement in the anti-fouling behavior. Highlights: PANI/PSF blend membranes (PPMs) were successfully fabricated by immersion phase inversion. PPMs exhibited better hydrophilicity, water flux, and anti-fouling property. Extended Derjaguin Landau Verwey Overbeek (XDLVO) theory was used to predict fouling behavior. Providing excellent theoretical proof of the improvement of PPMs' anti-fouling property. Abstract: To enhance the anti-fouling performance of polysulfone (PSF) membranes, polyaniline (PANI) nanofibers were used as additives in a facile method to prepare PANI/PSF blended membranes (PPMs). The fouling behavior between the membrane and natural organic matters (NOM) pollutant was further analyzed by implementing extended Derjaguin–Landau–Verwey–Overbeek (XDLVO) theory. Overall, the performance of the PPMs was improved in comparison with that of the pristine PSF membrane. The pure water flux of the PPM increased to 2.4 times that of pristine PSF, reaching up to 169 L·m −2 h −1 bar −1 . The tensile strength of the hybrid membranes also increased after the incorporation of PANI nanofibers. In particular, in anti-fouling measurement, the PPMs exhibited enhanced anti-fouling properties for filtration serum albumin (BSA), humic acid (HA) and sodium alginate (SA) solutions. The anti-fouling mechanism was analyzed by the interfacial interaction energy, which were obtained by applying the XDLVO theory. Results confirmed that there are reduced attractive interaction energies between the PPMs and NOM pollutants molecules in comparison to the interaction between the pristine PSF and NOM pollutants molecules.